LEGAL STATUS AND REGIME OF THE CASPIAN SEA: PROBLEMS AND DEFINITIONS (Archive of Conferences, 2021)
The article examines the prospects of the Caspian as an oil-producing region and its unique geographic position make it the edge of regional geopolitical contradictions, the significance of which extends far beyond the borders of the Caspian states proper. The author analyzes the problems of the Caspian region. Studied the foreign policy of Russia in the Caspian region, including the West